GAMBARAN TOTAL ANGKA BAKTERI PADA SUSU SAPI SEGAR DI KUD KECAMATAN DAU KABUPATEN MALANG - Ridha Nurhayati; Martini Martini; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Total number of bacteria in the sub-district Dauwas 2,2-3,6x106CFU/ml with 13,7% prevalence of diarrhea. The qualityof fresh milk is characterized by the total number of bacteria in accordance with SNI ≤1x106CFU/ml. The purpose of this study is to describetotal number of bacteria on fresh cow's milk on the KUD. This study was observational using cross sectional design. Respondents accounted for 36 officers and the observed sample is fresh milk in KUD. Data analyzed using distribution frequency. The results showed an average total number of bacteria fresh milkat the KUD is 5,8x107CFU/ml.The total number of bacteria that not accordance with SNI is 80,6% on poor hygiene respondents (73,7%), poor hygiene vehicles (85,0%), and the length of milk’s distribution time >2 hours (80,0%). Distribution officersshould give more attention to cleanliness of vehicles used for such distribution laundering vehicles before distribution.